Cement Supply Chain Model of Palangka Raya Using System Dynamics Method - Aulia, S; Waluyo, Rudi; Purwantoro, A (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2025)
One of the most strategic material resources in the execution of construction is cement. It is estimated that the demand for cement to support construction activities in Indonesia is approximately 78.66% of national cement consumption, with cement consumption in Indonesia increasing by 14.1% in the first quarter of 2021 to 18.19 million tons. The objective of this research is to understand how the dynamic supply chain model and cement inventory in Kota Palangka Raya will be from 2024 to 2028. In this research procedure, data analysis techniques use the system dynamic method with the Vensim program, utilizing data from interviews with distributors and retail stores scattered in Kota Palangka Raya and supporting research data. The results of the supply chain model for cement include three variables: stock, in, and out. The total inventory of Conch cement in 2024 is 1140555 zak, in 2025 is 1547654 zak, in 2026 is 6192387 zak, in 2027 is 1946944 zak, and in 2028 is 1918412 zak. The total inventory of Gresik cement in 2024 is 548287 zak, in 2025 is 1785559 zak, in 2026 is 1826060 zak, in 2027 is 1849395 zak, and in 2028 is 1838869 zak. The total inventory of Tiga Roda cement in 2024 is 42763390 zak, in 2025 is 250804 zak, in 2026 is 177705 zak, in 2027 is 321805 zak, and in 2028 is 183585 zak.